2018
DOI: 10.3389/fcimb.2018.00088
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nicotine Tolerance by Quorum Sensing and High Efficiency of Quorum Quenching Under Nicotine Stress in Pseudomonas aeruginosa PAO1

Abstract: Quorum sensing (QS) regulates the behavior of bacterial populations and promotes their adaptation and survival under stress. As QS is responsible for the virulence of vast majority of bacteria, quorum quenching (QQ), the interruption of QS, has become an attractive therapeutic strategy. However, the role of QS in stress tolerance and the efficiency of QQ under stress in bacteria are seldom explored. In this study, we demonstrated that QS-regulated catalase (CAT) expression and biofilm formation help Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…20 Our results showed that nicotine has a toxic effect on PAO depending on the concentration. Other reports have shown that nicotine modifies the composition and structure of the biofilms produced by PAO and also regulates the quorum sensing and quorum quenching, 3 nonetheless, the growth rates remained the same, suggesting that the growth induction effect induced by nicotine is specific for Mtb.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…20 Our results showed that nicotine has a toxic effect on PAO depending on the concentration. Other reports have shown that nicotine modifies the composition and structure of the biofilms produced by PAO and also regulates the quorum sensing and quorum quenching, 3 nonetheless, the growth rates remained the same, suggesting that the growth induction effect induced by nicotine is specific for Mtb.…”
Section: Discussionmentioning
confidence: 72%
“…For instance, the presence of nicotine in Pseudomonas aeruginosa (PAO) cultures promotes the formation of biofilms and the expression of other virulence factors. 3 Other studies have demonstrated that the presence of nicotine promotes virulence factors including those related to resistance to antimicrobial peptides (AMPs) in methicillin-resistant Staphylococcus aureus (MRSA); 4 however, there is scarce information regarding the effect that nicotine might have on Mycobacterium tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAT is an important antioxidant enzyme in bacteria exposed to xenobiotics. The activity of this enzyme has been observed in freshwater bacterial biofilms exposed to the herbicide oxyfluorfen ( Bonnineau et al, 2013 ), and P. aeruginosa PAO1 WT exposed to nicotine ( Tang et al, 2018 ). Despite the importance of CAT, other enzymes participate in the metabolism of H 2 O 2 , such as glutathione peroxidases ( Gebicka and Krych-Madej, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Tan module was enriched with 1 KEGG pathway and 5 biological processes (Table 1 and S5B Fig). Quorum sensing pathway enriched in Tan module is known to enhance stress responses in various organisms like V. cholerae [47], Pseudomonas aeruginosa PAO1 [48,49] as well as in D. radiodurans [50]. Besides this, the Tan module was also found to be enriched with the genes and proteins crucial for both gamma radiation and desiccation stress such as DR_0423 (Single-stranded DNA binding protein/DdrA) and DR_A0282.…”
Section: Plos Onementioning
confidence: 99%